Penerapan Sistem Informasi Administrasi Dalam Mewujudkan Efektifitas Kerja Organisasi Pada Dinas Sosial Kota Kendari - Saputri, Yeyen Aknes; Sartono, Sartono; Justawan, Justawan (REZ PUBLICA, 2021)
This study aims to describe the application of the Administration Information System Function in Realizing the Effectiveness of Organizational Work at the Social Service of Kendari City. The method used in this study is a qualitative descriptive method by means of observation, interviews and documentation. The results of this study indicate that the Application of Administrative Information Systems in Realizing Organizational Work Effectiveness at the Social Service of Kendari City still needs to be improved because there are still several indicators that need to be considered again such as indicators of data entry and data processing. In addition, the quality and efficiency of the Kendari City Social Service is considered to be less than optimal, especially the problem of timeliness needs to be improved again.